Scale Characteristics of Intercultural Competence Measures and the Effects of Intercultural Competence on Prejudice - Genkova, Petia; Schaefer, Christoph Daniel; Schreiber, Henrik; Rašticová, Martina; Poor, Jozsef; Veresné, Klara Valentinyi; Suhajda, Csilla; Viszetenvelt, Andrea; Bjekic, Jovana (Frontiers in Psychology, 2021)
Due to proceeding globalization processes, involving a rise in mobility and international interdependencies, the frequency and relevance of intercultural contact situations increases. Consequently, the ability to deal effectively with intercultural situations is gaining in importance. However, the majority of studies on measures of intercultural competence focuses on Western Europe and the United States or cultures of the Far East. For the present study, previously understudied Eastern European (former communist) cultures were included, by sampling in Hungary, Serbia, and the Czech Republic, in addition to (the Central or Western European country) Germany. Thus, this study enabled comparisons of scale characteristics of the cultural intelligence scale (CQS), the multicultural personality questionnaire (MPQ), as well as the blatant and subtle prejudice scales, across samples from different cultures. It was also examined how the CQS and MPQ dimensions are associated with prejudice. To analyse scale characteristics, the factor structures and measurement invariances of the used instruments were analyzed. There were violations of configural measurement invariance observed for all of these scales, indicating that the comparability across samples is limited. Therefore, each of the samples was analyzed separately when examining how the CQS and MPQ dimensions are related to prejudice. It was revealed that, in particular, the motivational aspect of the CQS was statistically predicting lower prejudice. Less consistently, the MPQ dimensions of open-mindedness and flexibility were statistically predicting lower prejudice in some of the analyses. However, the violations of measurement invariance indicate differences in the constructs' meanings across the samples from different cultures. It is consequently argued that cross-cultural equivalence should not be taken for granted when comparing Eastern and Western European cultures.